General equilibrium existence with asset-backed securitization - Mariano Steinert; Juan Pablo Torres-Martínez (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2004)
We propose a specification of a general equilibrium model with securitization of collateral-backed promises and discuss the role of physical collateral to avoid, in equilibrium, pessimistic beliefs about the future rates of default. Promises are pooled in either pass-through securities or collateralized loans obligations (CLO), allowing the existence of different seniority lev- els among tranches in the same CLO. In case of default, borrowers may also suffer extra-economic penalties, which are internalized into a structure of non-ordered preferences. In this context, we prove the existence of an equilibrium in that investors are not over-pessimistic about the payments of derivatives. JEL Codes: D52, D91
Keywords: 330; Asset Backed-Securitization; Extra-economic Default Penalties; Collateral; Non- ordered Preferences